C-type natriuretic peptide (CNP) in the paraventricular nucleus-mediated renal sympatho-inhibition - Zheng, Hong; Patel, Tapan A.; Liu, Xuefei; Patel, Kaushik P. (Frontiers in Physiology, 2023)
Volume reflex produces sympatho-inhibition that is mediated by the hypothalamic paraventricular nucleus (PVN). However, the mechanisms for the sympatho-inhibitory role of the PVN and the neurochemical factors involved remain to be identified. In this study, we proposed C-type natriuretic peptide (CNP) as a potential mediator of this sympatho-inhibition within the PVN. Microinjection of CNP (1.0 g) into the PVN significantly decreased renal sympathetic nerve activity (RSNA) (-25.8 ± 1.8 vs. -3.6 ± 1.5%), mean arterial pressure (-15.0 ± 1.9 vs. -0.1 ± 0.9 mmHg) and heart rate (-23.6 ± 3.5 vs. -0.3 ± 0.9 beats/min) compared with microinjection of vehicle. Picoinjection of CNP significantly decreased the basal discharge of extracellular single-unit recordings in 5/6 (83%) rostral ventrolateral medulla (RVLM)-projecting PVN neurons and in 6/13 (46%) of the neurons that were not antidromically activated from the RVLM. We also observed that natriuretic peptide receptor type C (NPR-C) was present on the RVLM projecting PVN neurons detected by dual-labeling with retrograde tracer. Prior NPR-C siRNA microinjection into the PVN significantly blunted the decrease in RSNA to CNP microinjections into the PVN. Volume expansion-mediated reduction in RSNA was significantly blunted by prior administration of NPR-C siRNA into the PVN. These results suggest a potential role for CNP within the PVN in regulating RSNA, specifically under physiological conditions of alterations in fluid balance.